SUSTAINABLE DESIGN: IN SEARCH OF MEANING (ResearchJet Journal of Analysis and Inventions, 2021)
Greening all society spheres is a response to the global challenges of our time. According to famous philosophers E.V. Girusova, I.K. Liseeva, a humanitarian transition is made from an era before an ecological to an ecological era; humanity is taking the test for spiritualized intelligence, and modern technogenic civilization - on the biosphere compatibility.